ABOUT JUSTIFICATION OF DECRIMINALIZING INSULT AND DEFAMATION: criminal (non)policy of Serbian legislator - Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In this paper the author tries to provide a critical view of arguments used by the legislator in the process of decriminalizing insult and defamation. He is of the opinion that there are few such arguments, and after subjecting them to scrutiny the author fails to find justification for any of the arguments, and for some of them he finds that they are not criminal policy arguments. The largest section of the paper is focused on an argument that civil law protection is sufficient to provide protection for human dignity and finds that such a thing is not possible by the very nature of the object of the protection because it does not provide protection for a thing but it rather protects equality of a person with all other persons. On the other hand the author provides an analysis of the meaning of the honor and reputation as values protected by law in modern society and concludes that our legislator has undermined their importance by providing only for civil law protection of such values. By arriving at a conclusion that the soundness of human spirit is inextricably connected to undisturbed honor and reputation, it compares it to the notion of a healthy body in the area of physical existence. As much as a man strives towards a healthy body, he strives even more to have a healthy spirit. The cure for a human spirit does not lie in nature as the cause of illness is not to be found there. The cure for harmed honor and reputation is in providing satisfaction because satisfaction restores shaken self-confidence. As one of the strong arguments in favor of criminal law protection of honor and reputation, the author points out that there are no other human values that a man may enjoy even after death, and that honor and reputation may even be achieved after death.